Welfare and Distribution Effects of Water Pricing Policies - Arjan Ruijs (Fondazione Eni Enrico Mattei (FEEM), 2007)
In this paper, distribution and welfare effects of changes in block price systems are evaluated. A method is discussed to determine, for a Marshallian demand function, equivalent variation in case of a block price system. The method is applied to analyze welfare and distribution effects of changing water prices in the Metropolitan Region of S\~ao Paulo. Results show that there is a trade off between average welfare and income distribution. A pro-poor price system may result in lower average welfare than a flat price system, but in higher individual welfare for the poor. Moreover, there is a trade off between revenues for the water company and income distribution. Even though pro-poor price systems may not be as good for average welfare as flat price systems, their direct effects on poverty are important. Introducing pro-poor price systems, however, may have financial consequences for the water companies.
Keywords: D63; Q25; Q56; 330; Water Demand; Welfare Economics; Equivalent Variation; Wasser; Nachfrage; Wasserpreis; Wohlfahrtsanalyse; Mikroökonomische Konsumfunktion; Sao Paulo (Stadt)